Endogenous Costs and Price-Cost Margins - Zhentang Zhang; Lars-Hendrik Röller; Damien J. Neven (Deutsches Institut für Wirtschaftsforschung (DIW), 2002)
Empirical work on price-cost margins often treats costs as exogenous. Allowing for endogenous costs when estimating price-cost margins is the topic of this paper. Methodologically, the endogenous cost model we propose leads to an additional equation that allows for the simultaneity in price setting in the product and the input market (labor in our case). In other words, the usual two-equation set-up (demand and first-order condition in the product market) is generalized to include a third equation, which endogenizes costs. We implement the model using data for eight European airlines from 1976-1994, and show that the treatment of endogenous costs has important implications for the measurement of price-cost margins and the assessment of market power.
Keywords: L93; L40; 330; endogenous costs; price-cost margins; rent sharing; airline industry; Gewinn; Betriebliche Preispolitik; Kosten; Lohnverhandlungstheorie; Luftverkehr; Oligopol; Schätzung; Theorie; Westeuropa; rent sharing